2007
DOI: 10.1590/s0101-20612007000500002
|View full text |Cite
|
Sign up to set email alerts
|

Extração e fracionamento simultâneo do óleo da castanha-do-Brasil com etanol

Abstract: ResumoO objetivo deste trabalho foi utilizar o etanol comercial para extração e fracionamento simultâneos das frações lipídicas presentes na castanha-do-Brasil (Bertholletia excelsea H.B.K.). O óleo foi obtido a partir da castanha desidratada e moída. O processo foi conduzido na proporção 4:1 solvente/substrato (v.p -1 ) em banho termostatizado a 65 °C, sob agitação de 30 rpm. A mistura foi filtrada, resfriada a 10 °C e, a seguir, centrifugada para separação das fases: uma fase com consistência de gel (micela … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
17

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 1 publication
0
13
0
17
Order By: Relevance
“…27,28 The oxidative metabolism can be evaluated by the quantification of oxygen consumption or the formation of derivatives from cellular oxidative metabolism, superoxide anion being among them. 29,30 In this context, Brazil nut stands out for presenting high content of oil (around 45,2%), comprising palmitic, stearic, oleic, and linoleic acids , 31 vitamins, minerals, [32][33][34] and other compounds, such as tannins, ellagic acid, curcumin, flavonoids, and isoflavones. 35 Then, the aim of this study was to develop and characterize a Brazil nut oil microemulsion system and evaluate the effect of this microemulsion on the superoxide release in human phagocytes.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 The oxidative metabolism can be evaluated by the quantification of oxygen consumption or the formation of derivatives from cellular oxidative metabolism, superoxide anion being among them. 29,30 In this context, Brazil nut stands out for presenting high content of oil (around 45,2%), comprising palmitic, stearic, oleic, and linoleic acids , 31 vitamins, minerals, [32][33][34] and other compounds, such as tannins, ellagic acid, curcumin, flavonoids, and isoflavones. 35 Then, the aim of this study was to develop and characterize a Brazil nut oil microemulsion system and evaluate the effect of this microemulsion on the superoxide release in human phagocytes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the 5-kDa PES membrane showed 62% phospholipid retention in miscella form (using anhydrous ethyl alcohol as a solvent), and required a long time to reach a CF (Kumar and Bhowmick, 1996;Freitas et al, 2007) which hinders the passage of miscella through the membrane, necessitating a longer time to reach a CF of 1.4, in addition to a sharp decrease in the flow and the probable onset of pore obstruction. The flow rates encountered in this study can be considered higher than those observed by Manjula and Subramanian (2009), who used non-porous membranes (2.04 kg·m…”
Section: Degumming Of Crude Rice Bran Oil In the Ultrafi Ltration Unitmentioning
confidence: 99%
“…In this sense, there is potentiality in the use of Brazil nut oil due to its rich lipid profile, which presents about 13.8% of palmitic acid; 8.7% stearic acid; 31.4% oleic acid and 45.2% linoleic acid, besides small amounts of palmitoleic and myristic acids (Gutierrez, Regitano-D'Arce, & Rauenmiguel, 1997;Freitas, Freitas-Silva, Miranda, & Coelho, 2007), all these fatty acids are considered as essential for the metabolic pathways of birds.…”
Section: Introductionmentioning
confidence: 99%